Polymeric mannosides prevent DC-SIGN-mediated cell-infection by cytomegalovirus. Issue 36 (5th September 2017) - Brument, S.; Cheneau, C.; Brissonnet, Y.; Deniaud, D.; Halary, F.; Gouin, S. G.
Abstract : Dextrans coated with triazolylheptylmannoside ligands block human cytomegalovirus trans -infection at picomolar polymer concentrations. Abstract : Human cytomegalovirus (HCMV) is a beta-herpesvirus with a high prevalence in the population. HCMV is asymptomatic for immunocompetent adults but is a leading cause of morbidity for new born and immunocompromised patients. It was recently shown that the envelope glycoprotein B (gB) of HCMV interacts with the Dendritic Cell-Specific ICAM-3 Grabbing Non integrin (DC-SIGN) to infect the host. In this work we developed a set of DC-SIGN blockers based on mono-, di-, tetra and polyvalent mannosides. The multivalent mannosides were designed to interact with the carbohydrate recognition domains of DC-SIGN in a chelate or bind and recapture process, and represent the first chemical antiadhesives of HCMV reported so far. Polymeric dextrans coated with triazolylheptylmannoside (THM) ligands were highly potent, blocking the gB and DC-SIGN interaction at nanomolar concentrations. The compounds were further assessed for their ability to prevent the DC-SIGN mediated HCMV infection of dendritic cells. A dextran polymer coated with an average of 902 THM ligands showed an outstanding effect in blocking the HCMV trans -infection with IC50 values down to the picomolar range (nanomolar when expressed in THM concentration). Each THM moiety on the polymer surpassed the antiadhesive effect of the methylmannoside reference by more than four orders of magnitude. The compound proved non-cytotoxic at the high concentration of 2 mM and therefore represents an interesting antiadhesive candidate against HCMV and potentially against other virus hijacking dendritic cells to infect the host.